Research on the Identification of Wheat Fusarium Head Blight Based on Multispectral Remote Sensing from UAVs - Dong, Ping (2024)
Dong, P., Wang, M., Li, K., Qiao, H., Zhao, Y., Bação, F., Shi, L., Guo, W., & Si, H. (2024). Research on the Identification of Wheat Fusarium Head Blight Based on Multispectral Remote Sensing from UAVs. Drones, 8(9), 1-18. Article 445. https://doi.org/10.3390/drones8090445 --- This research was funded by the Key Research and Development Project of Henan Province, China (241111110800); Natural Science Foundation of Henan Province, China (232300420186); Key Scientific and Technological Project of Henan Province (242102111193); National Natural Science Foundation of China (32271993); Joint Fund of Science and Technology Research Development program (Cultivation project of preponderant discipline) of Henan Province, China (222301420113, 222301420114); Key Research and Development Project of Henan Province, China (231111110100); and Henan Center for Outstanding Overseas Scientists (Project No. GZS2024006). FCT (Fundação para a Ciência e a Tecnologia), under the project-UIDB/04152/2020-Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS).